2022
DOI: 10.1172/jci156624
|View full text |Cite
|
Sign up to set email alerts
|

Sortilin drives hypertension by modulating sphingolipid/ceramide homeostasis and by triggering oxidative stress

Abstract: Sortilin is a glycoprotein mainly known for its role as a trafficking molecule directing proteins to specific secretory or endocytic compartments of the cell. Its actual contribution to essential hypertension has remained hitherto elusive. Combining top-notch in vivo, ex vivo, and in vitro approaches to clinical investigations, Di Pietro et al. explored the signaling pathway evoked by sortilin in endothelial cells and report on such exploration in this issue of the JCI . The researchers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 25 publications
2
14
0
Order By: Relevance
“…Hypertension (HT) is a major mortality reason affecting over a quarter of the world’s adult population (about one billion adults worldwide). Nadar et al estimated that by the end of 2025 this number will increase to over 1.5 billion.…”
Section: Effect Of Ros On Aging and Age-associated Diseasementioning
confidence: 99%
“…Hypertension (HT) is a major mortality reason affecting over a quarter of the world’s adult population (about one billion adults worldwide). Nadar et al estimated that by the end of 2025 this number will increase to over 1.5 billion.…”
Section: Effect Of Ros On Aging and Age-associated Diseasementioning
confidence: 99%
“…Thus, COVID-19 affects not only the epithelial cells of the lung 46 , 47 , but also endothelial cells across the whole body, leading to a generalized endothelial damage. Endothelial cells are known to play instrumental roles in the maintenance of vascular homeostasis and in the regulation of vascular tone 48 , 49 , 50 . Endothelial damage, caused directly by SARS-CoV-2 infection and/or by the ensuing inflammation, can shift the vascular equilibrium towards an altered vascular tone, an increased permeabilization, with subsequent tissue edema, and a pro-coagulant state, which can lead to thromboembolism; most of these findings have been substantiated by autopsies of COVID-19 patients since the outbreak of the pandemic 51 , 52 , 53 .…”
Section: Introductionmentioning
confidence: 99%
“…Serum sortilin was elevated in patients with coronary artery disease and carotid artery stenosis, and correlated with the severity of coronary artery disease and carotid plaque burden ( 8 , 15 ). It has been recently reported that sortilin changes sphingolipid/ceramide homeostasis and initiates the endothelial cell signaling pathway, resulting in increased production of reactive oxygen species (ROS), leading to increased arterial blood pressure ( 9 , 16 ). However, in a cohort study of 1,173 low- to intermediate-risk chest-pain patients, plasma sortilin was not associated with CAD severity and coronary calcium score, and sortilin did not improve existing risk stratification in the clinical environment ( 10 ).…”
Section: Discussionmentioning
confidence: 99%
“…Correlation analysis demonstrated that sortilin levels were significantly positively correlated with ET-1 levels and negatively correlated with NO levels in the general population. The imbalance between ET-1 and NO produced by vascular endothelial cells can cause endothelial dysfunction, elevated proinflammatory events, as well as increased oxidative stress, thus leading to the development of hypertension ( 16 , 20 , 21 ). It has been reported that sortilin induces ROS overproduction and endothelial dysfunction by activating the acid sphingomyelinase (ASMase)/sphingosine-1-phosphate (S1P) pathway ( 9 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation